A comparative analysis of electricity generation costs from renewable, fossil fuel and nuclear sources in G20 countries for the period 2015-2030. (20th October 2018) - Ram, Manish; Child, Michael; Aghahosseini, Arman; Bogdanov, Dmitrii; Lohrmann, Alena; Breyer, Christian
Abstract: Despite the positive momentum achieved by the renewable energy sector in recent years, there are substantial challenges that need the attention of the global community, and one of the more pressing issues is dealing with the deleterious external costs of power generation. One of the parameters to compare costs of energy across various technologies is levelised cost of energy (LCOE), but it has been conventional practice to neglect the external costs in estimating the LCOE of power generation technologies. Furthermore, as LCOE is a critical indicator for policy and decision makers, there is a need to juxtapose actual costs of renewable and conventional power generation technologies. This research paper attempts to internalise some of these external and GHG emission costs across various power generation and storage technologies in all the G20 countries, as they account for 85% of global power consumption. As future investment decisions are largely influenced by costs, estimates in this research prove renewables and storage to be far cheaper than fossil and nuclear sources by 2030, even without considering external costs. The myth that renewables are 'way too expensive' has been debunked repeatedly, and the cost decline of wind and solar photovoltaic (PV) technologies have outpaced most industry expectations. The results of this research not only substantiate this trend, but also statistically display that all the G20 countries have the opportunity to decrease their energy costs significantly, between now and 2030. Renewable energy technologies offer the lowest LCOE ranges across G20 countries in 2030. Utility-scale solar PV generally shows the lowest values ranging from 16 to 117 €/MWhel and onshore wind LCOE range is from 16 to 90 €/MWhel . Rooftop solar PV generally offers the next lowest LCOE ranging from 31 to 126 €/MWhel, followed by LCOE of offshore wind power ranging from 64 to 135 €/MWhel . Solar PV and battery systems are highly competitive on an LCOE basis at utility-scale ranging from 21 to 165 €/MWhel and at residential scale from 40 to 204 €/MWhel . The G20, as well as other countries, can continue to develop their economies in a sustainable manner, along with substantial co-benefits in adjacent policy fields such as higher national welfare, better health of citizens, lower respective health costs and improved energy security. Graphical abstract: Image 1